Multiple Severe Toxicities of L-Asparaginase and Their Innovative Management during Induction Therapy of Acute Lymphoblastic Leukemia in an Adult Patient - Guillaume Beziat; Suzanne Tavitian; Muriel Picard; Stanislas Faguer; Christian Recher; Françoise Huguet (Case Reports in Hematology)
L-asparaginase is a key chemotherapeutic agent in acute lymphoblastic leukemia (ALL). It is also known for multiple and severe specific toxicities, without consensual management. We report the case of a 51-year-old man treated with L-asparaginase for recently diagnosed T-cell ALL. During the treatment, he developed a coma due to multifactorial diffuse cerebral edema, by hepatic encephalopathy, cerebral venous thrombosis, and hyperammonemia, all linked to toxicity of L-asparaginase. Specific and innovative treatments were employed to manage these toxicities: supplementation with L-carnitine, thiamine, and pyridoxine for hepatic toxicity, perfusion of sodium benzoate to decrease ammonemia, and extrahepatic albumin-based dialysis sessions, along with anticoagulation. The patient improved within two weeks and is currently alive 13 months later, in first complete remission, without sequelae, on an alleviated chemotherapy regimen.